Studi Korelasi Obesitas dengan Kejadian Hipertensi pada Wanita Usia 40 - 60 tahun di Desa Kertosari Kecamatan Asembagus Kabupaten Situbondo - Muarrofah, Muarrofah (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2009)
This Paper explain to identify obesity, hypertension and identifies the relation of obesity with case of hypertension at age women 40-60 years in countryside Kertosari District Asembagus Sub-Province Situbondo. research applies design crossectional and sample is taken with technique concecutive samplingThe result from this research shows out of 30 women responders most of suffering obesity 1 but doesn’t suffer hypertension 11 (33,67%) and partly small or there is no responders experiences obesity 1 with weight hypertension, obesity 1 with hypertension maligna, obesity 11 with hypertension maligna, hardly obesity with hypertension maligna, each them has frequency.Keyword: obesity, hypertension, women 40-60 years